Organizational executions and policies on workplace health promotion: A cross-sectional study in Thailand - Taechamanodom, Taechit; Sithisarankul, Pornchai; Ratanachina, Jate (Chulalongkorn Medical Journal, 2024)
Background: The workplace exerts a profound effect on the health and well-being of the workforce, thereby assuming a pivotal role in both economic prosperity and societal advancement. Within organizational contexts, the human resources (HR) department assumes a pivotal role in the holistic care and administration of the workforce, encompassing multifaceted dimensions of health and well-being. However, studies on the executions and policies on workplace health promotion among HR executives and personnel in Thailand are limited. Objectives: This study aimed to investigate the execution and potential of health promotion policies in Thailand’s workplaces. Methods: A cross-sectional study was undertaken among the HR executives and personnel across 814 listed enterprises located in Rayong province and Chonburi province, Thailand between January and March 2023. All subjects completed a questionnaire covering information on general characteristics; and executions and policies on workplace health promotion. Bivariate, multiple linear regression and binary logistic regression analyses were used to identify the associated factors. Results: The response rate was 32.3%. Workplace health promotion executions demonstrated a statistically significant association with longer business operations (ß = 4.3; 95%CI 1.7 to 6.8), large-scale enterprises (ß = 4.9; 95%CI 1.7 - 8.2), and budget allocation (ß = 14.1; 95%CI 11.5 - 16.6). The workplace health promotion policies showed statistically significant associations with budget allocation for health promotion, including policies on employee involvement (OR = 4.2; 95%CI 2.4 - 7.3), physical environment (OR=5.7; 95%CI 3.2 - 9.9), psychological support (OR = 2.1; 95%CI 1.2 - 3.9), engagement and trust (OR = 3.8; 95%CI 2.2 - 6.5), management and leadership (OR = 5.2; 95%CI 2.9 - 9.0), work design (OR = 2.9; 95%CI 1.7 - 5.0), and monitoring and evaluation (OR = 3.7; 95%CI 2.0 - 6.6). Conclusion: The duration of organizational operations, organization size, and the allocation of budgetary resources for health promotion play crucial roles in determining the successful execution and feasibility of workplace health promotion policies within organizations.